Embodied cognition e origine del linguaggio: il ruolo cruciale del gesto (Lebenswelt. Aesthetics and philosophy of experience., 2019)
In this paper, we show how the embodied revolution within cognitive sciences has relevant consequences for the topic of language origins. The empirical findings of the embodied approaches, indeed, allow to elaborate a motor theory of language origins according to which human language originated from the gestural communication of our ancestors. Theories that propose that human language emerged from gesture suggest that an important stage in the evolution of human communication was that of pantomime, i.e. a spontaneous bodily mode of expression in which meaning is conveyed through resemblance. Adhering to this idea, we suggest that pantomime can be considered a platform for the emergence of human communication as it is a primordial mode of expression to tell stories without language. Based on that, we maintain that the possibility to explain the advent of language with reference to pantomime represents a way to support a narrative model of language origins.